Selenium status in dairy cows and feed samples in Estonia - Malbe, M; Oinus, N; Praakle, K; Roasto, M; Vuks, A; Attila, M; Saloniemi, H (MTT, 2005)
Introduction: Knowledge about selenium content in Estonian food chain is limited as no systematic selenium study is ever done in Estonia. Aim of our study was to evaluate selenium status in dairy cows and feed samples. Materials and methods: Altogether, 17 commercial dairy herds from 13 Estonian districts were studied. Blood samples from ten cows in each farm were collected. From each farm grain sample was taken. Information about feeding of selenium containing feed supplements and grain origin was asked. Selenium content in grain and glutathione peroxidase (GPx) activity in haemolysed whole blood was analysed. Results and discussion: Mean GPx activity in cows was 92-1204 ŠÌKat/l. Dividing cows into selenium-deficient (GPx¡Ü472 ŠÌkat/L) and non-deficient (GPx>472 ŠÌkat/L) group, it came evident that 66% cows were seleniumdeficient and only 34% of the cows belonged to the non-deficient group. Locally grown grain was used in 10 farms. Selenium content in local grain was below 0.02 mg/kg dw in 6 samples and 0.04-0.12 mg/kg dw in 4 samples. Selenium content in commercial grain was 0.37-0.90 mg/kg dw (n=7). Selenium containing mineral feed was used in 9 farms. Results of our study confirm the presence of selenium-deficiency in plant-animal chain in Estonia. Selenium status in Estonian food chain must be monitored to decide on the most effective way of selenium supplementation.
Keywords: Ka; Selenium; glutathione peroxidase; dairy cow; bovine; grain; feed